Impact of Differing Welfare Models on the Theoretical Framing and Implementation of Physical Accessibility - Shanon Wangner Santoso; Silfia Asning Tias (Universitas Negeri Surabaya, 2026)
Despite the global shift toward a social model of disability that emphasizes removing environmental barriers, many countries still struggle to translate legal rights into accessibility. This study examines how different national welfare systems, such as the productivist model in Japan and the rights-based model in Indonesia, impact the actual implementation of disability infrastructure. Using a qualitative comparative case study and a Most Different Systems Design (MDSD), this research analyzed primary legal documents and official reports from the 2024-2025 period. The findings reveal a significant social policy paradox in both nations. In Japan, productivist focus on economic utility has created adequate physical infrastructure, yet has resulted in social isolation in individuals. Conversely, Indonesia’s rights-based approach provides strong humanistic rhetoric but suffers from policy decoupling, where progressive laws are not matched by material reality, and further sustained by deep-rooted familialism. Therefore, the study concludes that both countries must move beyond purely economic or symbolic goals toward Implementation Engineering. By adopting an interactional understanding of disability, policymakers can bridge the gap between legal rhetoric and physical actuality to create a genuine architecture of belonging.